Menstrual cycle related changes in the laterality of the line orientation task - Hromatko, Ivana (2009)
Activational effects of sex hormones on spatial ability have been well documented. It has been suggested that these effects might be related to hormonally induced changes in interhemispheric communication, i.e. changes in laterality. Lateralization of spatial processing has mostly been studied with mental rotation tasks, while other types of spatial cognitive functions have been somewhat neglected. In this study we used a line orientation task in which lines at different angles to the horizontal were presented and had to be identified on a screen showing 24 different line angles. A group of healthy young women was tested twice, in different phases of menstrual cycle: luteal (high estrogen and progesterone) and menstrual (low levels of sex hormones). The EEG was being recorded while the participants were solving the tasks. Since it has been shown that higher alpha band (11-13 Hz) is sensitive to changes in the spatial demands of a task, we calculated the laterality scores (lnR– lnL) for this part of the EEG spectrum. As predicted, the laterality scores were significantly higher in menstrual compared to luteal phase of cycle, indicating higher lateralization of this specific spatial function in menstrual phase of cycle.